Kraftstoffverbrauch beim landwirtschaftlichen Transport - Maack, Christian; Büscher, Wolfgang (agricultural engineering.eu, 2008)
The conservation of feed crops in silage bags has been developed as an alternative operating technology to clamp silos. With the development of the technology to higher throughput it can be employed in harvesting systems with higher performance. Similar to other silage technologies the crop compaction has important effect on silage quality. To evaluate the crop compaction for the bagging technology, measurements at silages of sugar beet pulp, maize and maize ear silage were made.